The Effect of Employee Competency and Training on Employee Performance With Organizational Citizenship Behavior (OCB) as A Mediating Variable in The Regional Inspectorate of The Riau Islands Province - Muhammad Donal Mon; Saharuddin Saharuddin; Agustinus Setyawan (Dinasti Publisher, 2025)
The best performance of employees is the basis for an organization’s achievement in achieving goals, especially in the government sector. This study emphasizes the importance of employee competence and training in increasing employee performance with OCB as one of the factors that affect this relationship in Regional Inspectorates throughout Riau Islands Province. This research uses primary data and census sampling with a sample of 300 functional employees of Auditors and PPUPD at Regional Inspectorates throughout the Riau Islands Province. This research uses quantitative techniques as a research design. Data collection was established by dispersing questionnaires online.This research outcomes show that competence and training have a significant impact directly on employee performance, OCB has a significant impact on employee performance. Competence and training have a significant effect on OCB, the indirect influence of employee competence and training on mediated employee performance can be stated that OCB has succeeded in mediating the influence of employee competence and training on employee performance significantly.